The value of vaccination: results of an Italian survey among Medical Doctors, Policy Makers and General Population (Italian Journal of Public Health, 2012)
Background: In the Italian context, evolving toward the abandonment of compulsory vaccination, themaintenance of adequate levels of coverage appears as essential. The promotion of a good vaccinationknowledge, supported by strong scientific evidence, and the collaboration of all the involved stakeholders,appears hence fundamental. The aim of this survey was to understand why vaccination is not appreciatedfor its real value by different stakeholders.MeThods: In collaboration with other Italian universities and health districts, in summer 2011 we submit-ted a survey of 17 questions to a convenience sample of Italian Medical doctors, Policy Makers and generalPopulation. The main questions analyzed the importance of vaccination for health, actions to attain vac-cination value and consequences of a free choice policy.resulTs: of the 173 stakeholders interviewed, 78% of Medical doctors, 82% Policy Makers and 46%general Population believe that vaccination is important for health. The most important actions suggestedfor strengthening vaccination were information about its efficacy and safety and studies on its impact onPublic health, according to most of general Population and of Medical doctors and Policy Makers, respec-tively. according to 60.4% Medical doctors, 72.8% Policy Makers and 56.3% general Population the aboli-tion of compulsory vaccination would lead to a reduction of vaccinees in all the Italian regions.conclusIons: our study confirms the need for a thorough “education in vaccination”. among stakehold-ers there are still doubts that hinder the decision process about vaccination policies and programmes. onthe other hand, a call for an “alliance” for promoting and implementing vaccination to its full potentialwould be favoured, as sustained by a right understanding and attitude towards vaccines.
Keywords: Vaccination; Knowledge; Attitude; Behaviour; Survey